Penerapan Pendidikan Kristen Konteks Keluarga Dalam Menanamkan Karakter Jujur Pada Anak Di TK Kristen Petra Terpadu - Natalia Natalia; Ahmad Tabrani (Sekolah Tinggi Teologi Nusantara, 2021)
Christian education in the context of the family is very important to do because the family is a place formed by God for a child to be brought up to be educated in the knowledge of God and grow in character. Honest character is very important to be instilled and formed in children. Because honesty will be the main capital for someone to be trusted by others. Trust that will be the basis for social relations, whether family, friendship or in work or business relationships. This study uses a qualitative type of research through interviews with parents of TK A children, namely eight family informants who are Christian. Methods of data collection using interviews. The results of the study found that family context Christian education in Petra Terpadu Christian Kindergarten had not been implemented by all families. Of the eight families who were respondents, there were only two families that were categorized as very good in implementing Christian education in the family. Meanwhile, the other six families were considered to be lacking in implementing Christian education in the family. The results of the study on eight children of Petra Integrated Christian Kindergarten A showed that a small number of children showed honest character in the good category and most (six children) did not show honest character. The results also show that families who apply Christian education in the family show a very good honest character, while families who are not good at implementing Christian education in the family show honest character in their children. This shows that Christian education in the family has an impact on the formation of honest characters in children. Where is the exemplary factor of parents in quotes and factors of action that really determine the honest character of the child.